Jabuticaba [Plinia trunciflora (O. Berg) Kausel] Protects Liver of Diabetic Rats Against Mitochondrial Dysfunction and Oxidative Stress Through the Modulation of SIRT3 Expression - Calloni, Caroline; Martínez, Luana Soares; Gil, Daniela Franciele; da Silva, Douglas Machado; Jahn, Matheus Parmegiani; Salvador, Mirian (Frontiers in Physiology, 2021)
Complications generated by hyperglycemia present in diabetes mellitus (DM) have been constantly related to oxidative stress and dysfunction in the mitochondrial electron transport chain. Sirtuin 3 (SIRT3), which is present in mitochondria, is responsible for regulating several proteins involved in metabolic homeostasis and oxidative stress. Studies have suggested alterations in the expression of SIRT3 in diabetes. The objective of this study was to evaluate the effects of phenolic compounds in jabuticaba (Plinia trunciflora), a berry native to Brazil, on the activity of mitochondrial electron transport chain complexes, SIRT3 protein expression and oxidative stress parameters in liver of diabetic rats induced by streptozotocin. After type 1 DM induction (streptozotocin 65 mg/kg), diabetic and healthy rats were treated with jabuticaba peel extract (JPE) by gavage (0.5 g/kg of weight) for 30 days. After treatments, that diabetic rats presented impaired activities of complexes I, II, and III of electron transport chain along with an overexpression of SIRT3. In addition, an increase in lipid peroxidation and superoxide dismutase and catalase activities was observed in the diabetic group. The treatment with JPE was able to recover the activity of the mitochondrial complexes and reduce the expression of SIRT3. Furthermore, JPE treatment reduced oxidative damage to lipids and brought the antioxidants enzyme activities to basal levels in diabetic rats. Together, these results demonstrate that JPE can reduce oxidative stress related to DM by restoring mitochondrial complexes activity and regulating SIRT3 expression. Thus, JPE could become an alternative to reduce the development of complications related to DM.